ANALISIS STRATEGI PROMOSI DAN PELAYANAN WISATA GUNA MENINGKATKAM JUMLAH PENGUNJUNG DIPANTAI MUARO SASAK DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Mela Aliani; Sandra Dewi (CV. Adiba Aisha Amira, 2025)
Tourism is one of the strategic sectors in regional economic development. Pantai Muaro Sasak, as a tourist destination, has significant natural potential but faces challenges in increasing visitor numbers. This study aims to analyze the promotional strategies and tourism services implemented at Pantai Muaro Sasak and evaluate their alignment with Islamic business ethics principles. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with tourism managers, direct observations, and document studies. The findings indicate that the promotional strategies implemented include digital marketing through social media, partnerships with travel agencies, and organizing tourism events. Meanwhile, tourism services focus on hospitality, cleanliness, and visitor safety. From the perspective of Islamic business ethics, the promotional strategies and tourism services at Pantai Muaro Sasak reflect the principles of honesty (ṣidq), justice (‘adālah), and public benefit (maṣlaḥah). However, some aspects require improvement, such as price transparency and the enhancement of Sharia-compliant facilities. This study provides recommendations for tourism managers to enhance the effectiveness of digital promotions, improve services in accordance with Islamic principles, and develop halal tourism facilities to attract more Muslim tourists.